Analysis of Students’ Needs Related to their Learning Preferences - Nisrawati, Wa Ode (Master Program in Linguistics, Diponegoro University, 2018)
The objective of this research was to find out the Islamic Economy students’ needs and wants in learning English at State Islamic University of Pekalongan. The researcher used questionnaire to investigate and elicit opinion related to the needs, demands for English skills and preference of English learning activities, difficulties and barriers encountered by the students in learning English. The result reveals that most students show high demand on the speaking skill and want to develop it more. Besides, this research reveals that the students are facing difficulties and problems in communication because of the lacks of vocabulary, speaking skill, and grammar. Considering this result, it is suggested that the instructor/lecturer need to give more input of vocabularies especially vocabularies related to students’ major and occupational purposes.